2018
DOI: 10.1007/s10554-018-1507-x
|View full text |Cite
|
Sign up to set email alerts
|

Can stress echocardiography identify patients who will benefit from percutaneous mitral valve repair?

Abstract: The aim of the current study was to investigate whether stress echocardiography improves selection of patients who might have clinical benefit from percutaneous mitral valve repair with the MitraClip. In total, 39 patients selected for MitraClip implantation underwent preprocedural low-dose stress (dobutamine or handgrip) echocardiography from which stroke volume, ejection fraction and MR grade were measured. Outcome after MitraClip implantation was determined by New York Heart Association classification and Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In addition, HG has been used in echocardiography as a means of stress test to identify exertion induced ischemia or exertion induced left ventricular diastolic dysfunction [ 2 , 3 ]. Furthermore, HG has been used in combination with dobutamine stress echocardiography to identify patients with MR who would probably benefit from percutaneous mitral valve repair [ 4 ]. However, there is no existing data describing the effect of isolated HG on the severity of MR.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HG has been used in echocardiography as a means of stress test to identify exertion induced ischemia or exertion induced left ventricular diastolic dysfunction [ 2 , 3 ]. Furthermore, HG has been used in combination with dobutamine stress echocardiography to identify patients with MR who would probably benefit from percutaneous mitral valve repair [ 4 ]. However, there is no existing data describing the effect of isolated HG on the severity of MR.…”
Section: Introductionmentioning
confidence: 99%
“…In secondary MR, an exercise increase in EROA > 0.13 cm 2 and sPAP > 60 mmHg carry a poor prognosis [12] , while MR decrease with exercise because of improvement of walls motion, recruitment of ischemic segments, and ultimately reduction of the tethering forces could identify patients who would benefit from optimal medical therapy and revascularization prior to the correction of mitral disease [13] . On this basis, a study on 39 patients treated with MitraClip confirmed that a decrease in MR grade during stress echo was associated with limited clinical benefit from the procedure [14] .…”
Section: Echocardiographymentioning
confidence: 96%
“…Stress echocardiography, beyond the definition of MR relevance, may also help to identify patients who derive benefit from MitraClip: subjects who experience a reduction in MR severity during preprocedural low-dose stress (dobutamine or handgrip) echocardiography remain more symptomatic after intervention compared with those presenting with stable or increased MR during preprocedural stress, likely because in these patients MR might have contributed less to their symptoms during exercise, thus explaining the lack of benefit from a technically successful MitraClip procedure ( 75 ). Similarly, stress echocardiography may identify the optimal timing of PMVR at an earlier stage: patients with moderate resting developing severe exercise-induced MR during handgrip echocardiography have an improved treatment response after MitraClip ( 76 ).…”
Section: Beyond Baseline Evaluation Of MV and Lv Morphologymentioning
confidence: 99%
“…However, clinical experience and published data also highlight the need to consider several additional factors, including the presence of severe RV dysfunction, advanced LV impairment (typically associated with very high BNP values), and an irreversible precapillary component of pulmonary hypertension ( 92 ), that can attenuate the benefit of PMVR and predict potential futility. Where doubt remains, functional testing to assess ventricular reserve ( 75 , 83 ) and dynamic RV-to-pulmonary circulation uncoupling ( 82 , 93 ) can be useful for further risk stratification. Furthermore, risk associated with ischemic MR has been more comprehensively described as an interaction between MR severity and myocardial infarct size by CMR imaging, lending an opportunity for improved risk stratification beyond LV volumes and clinical parameters, and for the individualization of treatment decision ( Figure 9 ).…”
Section: The Selection Of the Optimal Candidatementioning
confidence: 99%